2002
DOI: 10.1580/1080-6032(2002)013[0031:amsitw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Acute Mountain Sickness in Tourists with Children at Lake Chungará (4400m) in Northern Chile

Abstract: Our results indicate that children are extremely sensitive to hypoxia, as expressed by symptoms of AMS and significant desaturation. Our findings add to the available information regarding the problems encountered when ascending to high altitude with children and support the importance of close monitoring of young children during ascent to high altitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 10 publications
3
39
0
2
Order By: Relevance
“…For comparisons, all six children aged 6 months to 4 yrs and five out of 10 children aged 13-18 yrs had significant symptoms of AMS (defined by o3 points in the Lake Louise questionnaire) after one night at 3,500 m (very young children were evaluated with a modified questionnaire) [16]. Since no statistical correlation was found among AMS scores and measures of periodic breathing in the current study, an interaction between periodic breathing and severity of AMS symptoms seems unlikely or weak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparisons, all six children aged 6 months to 4 yrs and five out of 10 children aged 13-18 yrs had significant symptoms of AMS (defined by o3 points in the Lake Louise questionnaire) after one night at 3,500 m (very young children were evaluated with a modified questionnaire) [16]. Since no statistical correlation was found among AMS scores and measures of periodic breathing in the current study, an interaction between periodic breathing and severity of AMS symptoms seems unlikely or weak.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ventilatory instability and periodic breathing have been shown to depend on the proximity of the eupnoeic carbon dioxide tension (PCO 2 ) to the apnoeic and hypopnoeic threshold PCO 2 , as well as on the ventilatory sensitivity to CO 2 below eupnoea [14]. These factors may differ between children and adults and may affect ventilation, oxygenation and thereby well-being and performance at high altitude [15][16][17]. As respiratory adaptation to acute altitude exposure has not been studied in detail in children, the current authors performed unobtrusive breathing pattern recordings by calibrated respiratory inductive plethysmography and actimetry in pre-pubertal children and their fathers.…”
mentioning
confidence: 99%
“…Since different ascent speed, latitudes, and different diagnostic criteria were used, this is neither surprising nor contradictory (Schneider et al, 2002), but still might represent differences in individual susceptibility in different populations. Previous studies included much smaller numbers of children (Moraga et al, 2002;Moraga et al, 2008;Pradhan et al, 2009) compromising generalizability. As previously shown, there was no significant difference in AMS prevalence between females and males (Hackett et al, 1976;Maggiorini et al, 1990).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…2 More recently, age also has been proposed as a risk factor. 3 It has been suggested that the incidence and severity of AMS may be inversely related to climbers' age; brain swelling may be better tolerated by elderly individuals because of the smaller brain/cranial vault volume ratio. 4 • 5 There are few clinical data to substantiate this speculation, 6 however, and there is no information from a controlled study on the prevalence and time course of AMS in adolescents after rapid ascent by mechanical transportation to altitudes of ~3 500 m, at which major tourist destinations are located throughout the world.…”
Section: Absth/kfmentioning
confidence: 99%